Variabilidad geográfica y alozímica en Neritina latissima (Gastropoda: Neritidae) en Costa Rica - Valdez, Marta F. (1980)
A phenotypic study of shell color and molecular variation in the loci glucose-6-phosphate dehydrogenase (G-6-PD) and glucosephosphate isomerase (GPO in the estuarine gastropod Neritina latissima in four populations in the Pacific coast of Puntarenas, Costa Rica, confirmed that the variation in frequencies of the different morphs is regulated through predation. There was no apparent effect of climate or any other environmental factor. Eight polymorphic alleles were detected in G -6 -PD and fourteen in GPI with starch gel electrophoresis. In both cases the allelic frequencies differ among populations, but there are unique variants in each. The average heterozygosity (H) per locus and per population is very high, ranging between 0.76 and 0.82 in G-6-PD and 0.78 to 0.87 in GPI. No apparent association was found between the allozirnic variation and the different phenotypes. Possible evolutionary implications on these results are discussed.